Construction of porous NiCo2S4@CeO2 microspheres composites for high-performance pseudocapacitor electrode by morphology reshaping. (June 2021) - Zhu, Y.-R.; Li, X.-Z.; Lai, X.-Q.; Xie, Y.; Li, Y.-M.; Yi, T.-F.
Abstract: NiCo2 S4 microspheres consisting of nanoparticles were synthesized by a simple hydrothermal process, and then NiCo2 S4 @CeO2 microspheres consisting of nanosheets or nanoneedles-like structures were constructed by a morphology reshaping process for the first time. The introduction of CeO2 changes the nanoparticle morphology of NiCo2 S4, and forms incompact nanosheet and nanoneedle structures. The porous, incompact nanosheet or nanoneedle structures with enhanced specific surface areas not only accelerate the charge transfer but also facilitate the electrolyte diffusion and provide more active sites for the redox reactions. These merits endow outstanding electrochemical performances to NiCo2 S4 @CeO2 microspheres when used as electrode materials for electrochemical pseudocapacitor. Especially, NiCo2 S4 @CeO2 (6 wt%) microspheres consisted of nanosheets show a high specific capacitance of 1263.6 F g −1 with a retention rate of 81.1% at 20 A g −1 after 10, 000 cycles. Nonetheless, pristine NiCo2 S4 microspheres consisted of nanoparticles only show a high specific capacitance of 555.2 F g −1 with a retention rate of 63.5% at the same conditions. The first-principles calculation shows that the strong interactions between the NiCo2 S4 and CeO2 are favorable for the stabilization of the composite, being responsible for its good cycling performance. The result shows that the NiCo2 S4 @CeO2 microspheres are promising electrode materials for high-performance pseudocapacitor, and morphology reshaping and CeO2 modification are efficient ways to construct high-performance pseudocapacitor. Graphical abstract: Image 1 Highlights: NiCo2 S4 @CeO2 microspheres consisted of nanosheets are designed by a morphology reshaping for the first time. Strong chemical bonding between the NiCo2 S4 and CeO2 makes a charge redistribution at the interface. NiCo2 S4 @CeO2 microspheres exhibits promising potential application potential.